Imagining the Future: Continuities and Ruptures Between Utopianism and Dystopia; [Imaginando O Futuro. Continuidades E Rupturas Entre Utopismo E Distopia]; [Imaginando el Futuro. Continuidades y Rupturas Entre Utopismo y Distopía] - Retamal-Hernandez, C (Universidad Central, 2023)
This article examines the crisis of modern utopian imagination and the rise of dystopian narratives, by exploring the dialectic between utopia and dystopia. It also addresses the reflective function of utopian and dystopian thought on modernity, as well as its confluence with science fiction. Furthermore, it analyzes the nostalgic turn towards the past due to the closure of future horizons, represented by left-wing melancholy and retrotopia. The author concludes that we are witnessing the decline of utopian imagination in favor of dystopian imagination. However, our ability to envision alternative futures depends on understanding the dialectic between utopia and dystopia, so as not to be overwhelmed by discouragement and immobilization. © 2023 Universidad Central. All rights reserved.